A review of laser and light therapy in melasma - M.K. Trivedi, BS, BA; F.C. Yang, MD; B.K. Cho, MD, PhD (Wolters Kluwer, 2017)
Melasma is a dysregulation of the homeostatic mechanisms that control skin pigmentation and excess pigment is produced. Traditional treatment approaches with topical medications and chemical peels are commonly used but due to the refractory and recurrent nature of melasma, patients often seek alternative treatment strategies such as laser and light therapy. Several types of laser and light therapy have been studied in the treatment of melasma. Intense pulsed light, low fluence Q-switched lasers, and non-ablative fractionated lasers are the most common lasers and light treatments that are currently performed. They all appear effective but there is a high level of recurrence with time and some techniques are associated with an increased risk for postinflammatory hyper- or hypopigmentation. The number and frequency of treatments varies by device type but overall, Q-switched lasers require the greatest number of treatment applications to see a benefit. Vascular-specific lasers do not appear to be effective for the treatment of melasma. Ablative fractionated lasers should be used with caution because they have a very high risk for postinflammatory hypo- and hyperpigmentation. The use of nonablative fractionated laser treatments compared with other laser and light options may result in slightly longer remission intervals. Picosecond lasers, fractional radiofrequency, and laser-assisted drug delivery are promising future approaches to treat melasma. The goal of this review is to summarize the efficacy and safety of the most commonly used laser and light therapies to treat melasma, briefly present future laser-based treatment options for patients with melasma, and provide recommendations for treatment on the basis of the reviewed information.